Company Name Change and Stock Returns: The Case of Indonesian Public Companies - Wiwik Utami; Tatang Ari Gumayanti (The Indonesian Journal of Accounting Research, 2014)
Abstract: This study is aimed at analyzing the effect of changing the name made by Indonesian public companies from the year 2000 to the year 2010. Using an event study methodology, we tried to analyze the short-term impact on stock prices around the announcement date. The study shows that the company's name change does not affect on stock returns, expressed in the form of abnormal returns. The average abnormal return before the event is positive while after the event it is negative. This finding indicates that investors do not consider the change of name as significant information. Thus, new name adoption is not regarded as informative in the short term by investors.Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh perubahan nama yang dibuat oleh perusahaan publik Indonesia tahun 2000 sampai dengan tahun 2010. Dengan menggunakan metodologi studi peristiwa, kami mencoba menganalisis dampak jangka pendek pada harga saham sekitar tanggal pengumuman. Studi ini menunjukkan bahwa perubahan nama perusahaan tidak berpengaruh terhadap return saham yang dinyatakan dalam ukuran abnormal return. Rata-rata abnormal sebelum peristiwa adalah positif sementara setelah peristiwa adalah negatif. Temuan ini menunjukkan bahwa investor tidak menganggap perubahan nama sebagai informasi penting. Dengan demikian, adopsi nama baru tidak dianggap informatif dalam jangka pendek oleh investor.